The Development of Music-Accompanied Gymnastics to Improve Motor Skills in Early Childhood - Radiah Wakulu, Poppy; Priyanti, Nita (Journal of Islamic Education Students (JIES), 2025)
Motor skill development in early childhood is a vital aspect of supporting holistic child growth. This study aims to develop a music-accompanied gymnastics model designed to enhance motor skills in early childhood. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation phases. The results show that gymnastics accompanied by music is effective in improving children's motor skills, such as agility, coordination, imaginative thinking speed, rhythmic counting ability, as well as increasing motivation and participation in physical activities. Educators responded positively to the use of rhythmic music enhanced with percussion instruments such as castanets. These findings suggest that music-accompanied gymnastics can serve as an engaging and effective instructional strategy to support optimal motor development in early childhood